2008
DOI: 10.1051/forest:2008034
|View full text |Cite
|
Sign up to set email alerts
|

Évolution des stocks de carbone dans la biomasse des forêts belges entre 1984 et 2000

Abstract: -• Carbon sequestration in forest ecosystems is an important though still uncertain process in the global greenhouse gas balance.• We computed biomass organic carbon (BOC) stocks of spatially explicit forested landscape units (LSU) in Belgium based on data collected in the regional forest inventories of 1984 (Wallonia region only) and 2000 (Wallonia and Flanders). C stock changes between 1984 and 2000 were estimated for Wallonia.• The total BOC pool stored in Belgian forests in 2000 amounts to 57.8 Mt C in 6 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…At the same time, soil organic C stock (SOC) was 94.4 Tg C (Lettens et al 2008). Average BOC stocks are about 9-10 kg C m -2 (Table 4), and are similar to values reported for neighbouring countries (e.g.…”
Section: Carbon Cyclesupporting
confidence: 57%
See 2 more Smart Citations
“…At the same time, soil organic C stock (SOC) was 94.4 Tg C (Lettens et al 2008). Average BOC stocks are about 9-10 kg C m -2 (Table 4), and are similar to values reported for neighbouring countries (e.g.…”
Section: Carbon Cyclesupporting
confidence: 57%
“…Repeated assessments of BOC and SOC stocks over the last few decades have revealed that Belgian forests as a whole are a carbon sink, storing about 1.2 Tg C year -1 (64% BOC and 36% SOC) (Lettens et al 2005(Lettens et al , 2008Vande Walle 2007). This high sequestration capacity is likely due to the high forest production (probably due to the young ages of the Belgian forests) and to an approach to forest management that is more focused on C storage (Lettens et al 2005(Lettens et al , 2008.…”
Section: Carbon Cyclementioning
confidence: 99%
See 1 more Smart Citation
“…Our living biomass CS estimate of 87 Mg ha -1 is 8 and 18 % smaller than estimations for the year 2000 also based on RFIW data in Lettens et al (2008) andin Vande Walle et al (2005). The Vande Walle's estimate is derived from Belgian wood volume equations (Dagnelie et al 1999) in combination with Vande Walle's 'BEF1' biomass factor.…”
Section: Living Biomassmentioning
confidence: 99%
“…External databases are thus needed for estimating the total carbon stock of the forest and the carbon stocks of all pools separately. Soil pool can be equal to or even greater than tree biomass (Lettens et al 2008;Liski et al 2006;Nabuurs et al 2003). …”
Section: Introductionmentioning
confidence: 99%